Natural superfetation idiopathic abortion in Pasundan cattle - Widyastuti, Rini; Setiawan, Rangga; Hilmia, Nena; Ulum, Mokhamad Fakhrul (ARSHI Veterinary Letters, 2023)
Abortion in cows is a condition in which the foetus is unable to survive until it is born. This paper is the first report of a case of superfetated idiopathic abortion from natural mating that occurred in primiparous Pasundan cows. The cows were initially kept in a colony pen system and mixed between young bulls (n=10) and heifers (n = 18) for two weeks after moving the cows from the livestock pen in Ciamis Regency. Pregnancy occurs because of natural mating in heifers without a known age and pregnancy history. Two months later, a primiparous Pasundan cow was observed to show symptoms of vaginal bleeding and straining, accompanied by the expulsion of a small foetus (length ~ 25 cm, foetal age ~ 120 days) several hours later and had previously experienced an abortion with a large foetus (length ~ 36 cm, foetal age ~150 days). Primiparous Pasundan cows that experienced abortion were separated into individual pens to reduce stress and for further observation. The therapy given is antibiotics and multivitamins were administered as therapeutic agents.